Implementasi Kebijakan Seleksi Terbuka Jabatan Pimpinan Tinggi dalam Penerapan Sistem Merit - Turnip, Sonya Riama Bernadette; Indah Mindarti , Lely; Hayat , Ainul (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Implementation of the Open Selection Policy for High Leadership Positions in Implementing the Merit System (Study on the Implementation of PermenpanRB No. 15 of 2019) to realize better governance and bureaucracy. This study aims to examine the preparation, implementation and monitoring evaluation stages of the open selection of high leadership positions at the Indonesia Civil Service Commission and policy performance in the implementation of open selection policies in government agencies using the Van Meter Van Horn model including: standards and objectives, resources, interorganizational communication and enforcement activities, characteristics of implementing agencies, economic, social, political conditions and the disposition of implementors. The method used in this research is a qualitative approach. The implementation of selection aims to minimize the practice of corruption, collusion and Nepotism. Indonesia Civil Service Commission carries out the task of merit system well as seen from the open selection recommendations from 2015-2023 showing an increase.